A software environment for effective reliability management for pulsed power design. (July 2021) - Robinson, Allen C.; Drake, Richard R.; Swan, M. Scot; Bennett, Nichelle L.; Smith, Thomas M.; Hooper, Russell; Laity, George R.
Abstract: The reliable design of magnetically insulated transmission lines (MITLs) for very high current pulsed power machines must be accomplished in the future by utilizing a variety of sophisticated modeling tools. The complexity of the models required is high and the number of sub-models and approximations large. The potential for significant analyst error using a single tool is large, with possible reliability issues associated with the plasma modeling tools themselves or the chosen approach by the analyst to solve a given problem. We report on a software infrastructure design that provides a workable framework for building self-consistent models and constraining feedback to limit analyst error. The framework and associated tools aid the development of physical intuition, the development of increasingly sophisticated models, and the comparison of performance results. The work lays the computational foundation for designing state-of-the-art pulsed-power experiments. The design and useful features of this environment are described. We discuss the utility of the Git source code management system and a GitLab interface for use in project management that extends beyond software development tasks. Graphical abstract: Highlights: Verification and validation environment supports pulsed power design. Analyst and code errors understood from a conditional probability perspective. Integrated model comparison infrastructure provides significant benefits. Software development environment utilized for multi-disciplinary project integration.